From Closed Banking to Open Banking: Risks and Opportunities - Zeynalova, Aytan (PT. EQUATOR SINAR AKADEMIA, 2024)
Rapid digitalization and technological advances in the banking sector have moved away from the traditional closed banking model and brought open banking, which is a more open and innovative structure, to the agenda. This article examines the evolution of open banking in the financial sector and the risks and opportunities presented by this transformation. In the introduction part of the article, the purpose and importance of the research is emphasized by focusing on the transformation process in the banking sector and the definition of open banking. Within the scope of the research method, the current situation and future potential of open banking are evaluated by analyzing the data obtained through methods such as current literature review, source selection, surveys and interviews. One of the main sections of the article focuses on the key differences between closed banking and open banking models. The basic principles of closed banking operation and open banking are discussed in detail. This chapter sheds light on the fundamental changes in the industry by focusing on changes in technological infrastructure. Another important part of the research addresses the risks posed by open banking. Security and data privacy concerns, legal challenges, and competition and innovation risks are evaluated in detail in this section. On the other hand, the opportunities provided by open banking are also examined in a separate section. Issues such as improvements in customer experience, increase in financial product diversity and innovation opportunities highlight the positive changes in the sector. In the results and discussion section, the comparison of closed and open banking models, the future of open banking and expectations are evaluated. Additionally, suggestions are offered to reduce risks and evaluate opportunities. The solution section of the article addresses practical solutions such as security strategies in open banking applications, development of regulatory frameworks and training of bank employees. In the References section, basic sources on open banking, literature on transformation in the banking sector and current research on risk-opportunity analysis are presented as resources.